PENGARUH KINERJA BAURAN PEMASARAN JASA DAN MANAJEMEN KERELASIAN PELANGGAN TERHADAP KEUNGGULAN BERSAING SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN (SURVEI PADA PELANGGAN SELULER DI JAWA BARAT) - Heppy Agustiana Vidyastuti (Indonesian Journal of Economics and Business, 2011)
The development of telecommunications and information technology is growing very rapidly, which can provide various types of telecommunications services desired by customers. The existing condition, the cellular mobile telecommunications provider in Indonesia : Telkomsel, Indosat, XL Axiata (XL), Huthcisson (HCPT), Natrindo Telepone Seluler, Mobile-8, Smart Telecom and Sampoerna Telekomunikasi Indonesia. The number of providers in the mobile industry to create tight competition so each provider as much as possible to apply the concept of service marketing mix, customer relationship management, competitive advantage and loyalty. But in the reality there are many complaints from its customers indicating that the performance of the implementation of all concept mentioned above, still do not meet the customer needs and at the end customer loyalty is low. Its condition can be seen from the high churn rate subscribers from one penyelenggara to another penyelenggara.The objective  of this research are to: (1) Obtaining the results of studies on the performance of services marketing mix, customer relationship management, competitive advantage and customer loyalty on cellular industry  in West Java, (2) To test a conceptual model and study the effect of the performance of services marketing mix, customer relationship management Competitive advantage and customer loyalty on cellular industry  in West Java either partially or simultaneously.Based on the data to be collected, then the object of study or unit of analysis in this study is the cellular subscribers of cellular providers that operated in West Java region, classified in 4 criterias are dense urban, urban, suburban and rural area. Samples were taken by random cluster sampling technique with a sample size of 756  responden of cellular. Data used in this study are primary and secondary data. Primary data collection techniques by questionnaire, interview and observation. Research Type used is descriptive and verification method of explanatory survey. The model is analyzed using Structural Equation influence Modeilng (SEM) since the model is composed of a number of causal relationships between latent variables.The results showed that the performance of services marketing mix, customer relationship management, competitive advantage and customer loyalty of cellular providers is good, and there is a significant effect between service marketing mix, customer relationship management, competitive advantage and customer loyalty.